Analyzing the sales force management system (project outreach) of Philip Morris Bangladesh Ltd. at Dhanmondi territory - Sadik, Imam Jafar (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.